A creative computing approach to 3D robotic simulator for water pollution monitoring. (1st January 2013) - Oyekan, John; Lu, Bowen; Hu, Huosheng
This paper presents a creative computing approach to the development of a 3D robotic simulator that could be used to develop control algorithms for a team of robotic fishes to effectively monitor water pollution. The computational fluid dynamics of a marine environment is taken into consideration, which differs from most existing robotic simulators and shows its creativity. It is the first 3D robotic simulator that enables users to develop control and navigation algorithms for pollution monitoring by a school of biologically inspired robot fishes. Additionally, this simulator has an interface to force fields and provides the diversity of simulation scenarios. The record-and-replay strategy is deployed in the simulator so that the fluid computation is done offline and recorded into a log file, which can then be replayed during a simulation. Experiments were conducted and results show that the proposed approach is feasible and has potential to be developed for a wider range of underwater applications.